Investigation of an attack on the multi-prime RSA cryptosystem based on cubic equations - Michalkovič, Aleksėjus; Žitkevičius, Jokūbas (Lietuvos matematikos rinkinys, 2023)
In this paper we consider a modification of the attack on the classic RSA cryptosystem aimed at factoring the public modulus n, which is a product of three primes. To improve the performance of the modified attack we introduce additional parameters. We present the theoretical upper bound on the search range parameter and define a shifting parameter based on the empirical results. Since these changes make our attack probabilistic, we investigate the dependence of the success on the values of the newly defined parameters.
Keywords: asymmetric cryptography; multi-prime RSA; integer factorization problem